Patient‐reported outcomes after cryoballoon ablation are equivalent between moderate sedation and general anesthesia. (27th May 2020) - Wasserlauf, Jeremiah; Kaplan, Rachel M.; Walega, David R.; Arora, Rishi; Chicos, Alexandru B.; Kim, Susan S.; Lin, Albert C.; Verma, Nishant; Patil, Kaustubha D.; Knight, Bradley P.; Passman, Rod S.
Abstract: Introduction: Moderate sedation (MS) during cryoballoon ablation (CBA) avoids risks of general anesthesia (GA) and improves electrophysiology (EP) lab throughput. However, one barrier to the use of MS is the potential for patient discomfort. The objective of this study was to compare patient‐reported outcome measures following CBA for paroxysmal atrial fibrillation (pAF) under MS and GA. Methods and Results: Consecutive patients undergoing a first CBA for pAF under GA or MS were prospectively enrolled. The sedation method was assigned based on patient and provider preference, and perceived airway risk. The primary outcomes were quality of recovery (measured using a validated 40 question survey; QoR‐40) and likelihood to recommend (LTR) the procedure and sedation method (measured by Likert scale). Secondary outcomes were acute pulmonary vein (PV) isolation rate, procedure, fluoroscopy and ablation times, and complication rates. Forty‐seven GA and 53 MS patients were included. The mean age was 64.9 ± 9.4 years and mean CHA2 DS2 ‐VASc score was 2.0 ± 1.4. QoR‐40 scores were 184.6 ± 16.4 for GA and 187.6 ± 10.2 for MS ( P = .28). LTR responses were similar between groups. Mean procedure times were 148.2 ± 56.0 minutes for GA and 129.4 ± 31.4 minutes for MS ( P = .038). Fluoroscopy and ablation times were similar between groups. A total of 100% (409/409) of PVs were acutely isolated. One hemopericardium occurred in the MS group requiring pericardiocentesis. Conclusion: MS for CBA offers an alternative to GA that is safe and well‐tolerated by patients with comparable success rates and improved EP lab throughput.